Neoadjuvant Treatment in Muscle-Invasive Bladder Cancer: From the Beginning to the Latest Developments - Roviello, Giandomenico; Catalano, Martina; Santi, Raffaella; Santoni, Matteo; Galli, Ilaria Camilla; Amorosi, Andrea; Polom, Wojciech; De Giorgi, Ugo; Nesi, Gabriella (Frontiers in Oncology, 2022)
Urothelial carcinoma of the bladder is one of the most prevalent cancers worldwide, diagnosed as muscle invasive in 25% of cases. Although several studies have demonstrated an overall 5% absolute survival benefit at 5 years with cisplatin-based combination neoadjuvant treatment, administration of chemotherapy prior to radical cystectomy (RC) in muscle-invasive bladder cancer (MIBC) patients is still a matter of debate. This may be due to the perceived modest survival benefit, cisplatin-based chemotherapy ineligibility, or fear of delaying potentially curative surgery in non-responders. However, immunotherapy and novel targeted therapies have shown to prolong survival in advanced disease and are under investigation in the neoadjuvant and adjuvant settings to reduce systemic relapse and improve cure rates. Genomic characterization of MIBC could help select the most effective chemotherapeutic regimen for the individual patient. Large cohort studies on neoadjuvant treatments with immune checkpoint inhibitors (ICIs) and molecular therapies, alone or combined with chemotherapy, are ongoing. In this review, we trace the development of neoadjuvant therapy in MIBC and explore recent advances that may soon change clinical practice.